Explanatory Factors of the Environmental Disclosure of Potentially Polluting Companies: Evidence From Brazil - Lívia Maria da Silva Santos; Wenner Glaucio Lopes Lucena; Wesley Vieira da Silva; Tatiana Marceda Bach; Claudimar Pereira da Veiga (SAGE Open, 2019)
This research aims at identifying explanatory factors of the environmental disclosure of potentially polluting Brazilian companies listed on the São Paulo Security, Commodities, and Futures Exchange (BM&FBOVESPA), from 2005 to 2015. Financial and environmental disclosure information of 182 Brazilian companies of the high-, medium-, and low-polluting potential sectors were collected. Data were analyzed through content analysis of documents and Regression with Panel Data. Results indicate that the company’s size, profitability, internationalization, and sustainability report are explanatory factors of the disclosure of environmental information, while indebtedness presents an inverse relationship. This study concludes that the explanatory factors of environmental disclosure of potentially polluting Brazilian companies are, with a higher weight, the publication of the sustainability report and stock market internationalization and, with lower weight, size, indebtedness, and profitability. This study discusses the relevance of environmental disclosure to companies that perform potentially polluting activities to provide support for different agents linked to these companies they may have access. It presents as theoretical contribution the explanatory variables for environmental disclosure of potentially polluting companies, an analysis not yet carried out in the literature. The practical contribution is to present information to interested users that potentially polluting companies, larger in size, internationalized, and with more profitability, disclose their environmental information.